2021
DOI: 10.1016/j.jcjo.2020.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Creating aerosolized droplets in phacoemulsification

Abstract: Creating aerosolized droplets in phacoemulsification A wetlab was set up using porcine eyes, an artificial anterior chamber maintainer, and an Alcon Infiniti phacoemulsification system (Fort Worth, TX; Fig. A). Colouring dye was placed in the irrigation fluid for easy identification of droplets on a white paper surface surrounding the eye. During simulated phacoemulsification, droplet/aerosol production occurred when the irrigation ports were in the incision, but not when they were entirely within the anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous studies suggest that any aerosol droplets can potentially deliver nucleic acids [ 4 8 ]. The release of aerosol from experimental phacoemulsification was previously reported using real-time imaging or luminol techniques [ 17 21 ]. A porcine-eye mock-up showed that phacoemulsification is a low-risk aerosol-generating procedure, which is also supported by the low transmission risk for SARS-CoV-2 by tears [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that any aerosol droplets can potentially deliver nucleic acids [ 4 8 ]. The release of aerosol from experimental phacoemulsification was previously reported using real-time imaging or luminol techniques [ 17 21 ]. A porcine-eye mock-up showed that phacoemulsification is a low-risk aerosol-generating procedure, which is also supported by the low transmission risk for SARS-CoV-2 by tears [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%